Conditions that Aggravate and Facilitate Assessment of Migrant Students - Nocetti de la Barra, Alejandra Viviana (2021)
The rising migrant student population in Chile´s school system has shed light on how intercultural perspectives are woven in teaching-learning processes and, specifically, how these conditions impact learning assessment. The objective involved analysis of conditions that both aggravate and facilitate assessment of migrant students at schools in the province of Concepción, Chile. Research for the study involved an interpretive focus given its emphasis on teacher experience. Research methodology was based on an instrumental case study using a multiple case design and semi-structured interviews with five high school teachers, selected through purposeful sampling. The data collected was subject to content analysis which contemplated a priori and emergent categories and subcategories, subsequently represented in two formats. Results indicate that interpersonal relationships and assessment accommodations comprise conditions that facilitate evaluation, since they help strengthening the student-teachers pedagogical relationship and foster greater awareness as to the particularities each student. However, lack of initial teacher training or extension education among teachers juxtaposed with few educational guidance at the Ministry level tend to hinder assessment of migrant students, given that teachers state not having proper guidelines to steer their teaching and evaluation practices. Although more preparation is needed when preparing student assessments, teaching practices in the classroom should reflect the cultural diversity of the students. A recommendation for teachers is to compare the national curriculum with that of the country of origin of the student to gauge relevant interventions.  Greater consideration of affective and attitudinal aspects must also be considered for purposes of assessments as well as more opportunities available to instructors so they can share teaching experiences from a more inclusive perspective that also appreciates practical knowledge.